Modeling and forecasting of injected fuel flow using neural network - Z., Saad; M. K., Osman; S., Omar; Mohd Yusoff, Mashor, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/